Effect of thiamine supplementation on glycaemic outcomes in adults with type 2 diabetes: a systematic review and meta-analysis - Ritin Fernandez; Heidi Green; Arti Muley; Prasad Muley (BMJ Open)
Background Patients with type 2 diabetes mellitus (T2DM) have been shown to have thiamine deficiency. Dietary supplementation is an economic strategy to control blood glucose. Objective: To evaluate effectiveness of thiamine supplementation on glycaemic outcomes in patients with T2DM.Methods Eligibility criteria: Studies that assessed effect of thiamine supplementation in adults with T2DM which measured glycaemic outcomes—HbA1c, fasting blood glucose (FBG) and/or postprandial blood glucose (PPG) were included. Information sources: PUBMED, Tripdatabase, the Cochrane Central Register, National Institute of Health Clinical Database and Google Scholar were searched until December 2021 for RCTs. Risk of bias: It was assessed using standardised critical appraisal instruments from the Joanna Briggs Institute for RCTs. Synthesis of results: Where possible, studies were pooled in a meta-analysis. Results were presented in a narrative format if statistical pooling was not possible.Results Included studies: Six trials involving 364 participants. Synthesis of results: No significant beneficial effects were observed on glycaemic outcomes with 100–900 mg/day of thiamine or benfotiamine for up to 3 months (HbA1c: MD, −0.02%, 95% CI: −0.35 to 0.31; FBG: MD,−0.20 mmol/L; 95% CI: −0.69 to 0.29; PPG: MD, – 0.20 mmol/L, 95% CI: −2.05 to 1.65 (mean difference, MD)). There was a significant increase in high-density lipoprotein (HDL) (MD, 0.10; 95% CI: 0.10 to 0.20) at 3-month follow-up. Benfotiamine reduced triglyceride level (MD, −1.10; 95% CI: −1.90 to –0.30) in 120 mg/day dose as compared with placebo 150 mg/day, however this was not demonstrated in higher doses.Discussion Limitations of evidence: Inclusion of single-centre trials published only in English, small sample sizes of included studies, lack of trials investigating outcomes for same comparisons and varying follow-up periods. Interpretation: Thiamine supplementation does not affect glycaemic outcomes, however reduces triglycerides while increasing HDL. Multicentre well-designed RCT with higher doses of thiamine and a follow-up period of 1–2 years will provide better evidence.PROSPERO registration number CRD42020170520.